A Web-Based Simulator for Leak Detection Problems in Water Distribution Pipes Using Vibro-Acoustic Techniques - de Almeida, Fabrício César Lobato [UNESP]; Brennan, Michael John [UNESP]; Iwanaga, Maurício Kiotsune [UNESP]; de Oliveira Cézar, Sillas [UNESP]; Bispo, Luís Armando Ferreira [UNESP]; Scussel, Oscar [UNESP] (Springer Nature, 2025)
Reduction of non-revenue water is one of the main goals of the water industry. It is estimated that 40% of water pumped via distribution systems in Brazil is lost, but there are states which have losses of 70%. One way of minimizing this problem is by massive investment in replacing old metallic pipes by plastic pipes made from PVC (Polyvinyl Chloride) and HDPE (High Density Polyethylene) material. Furthermore, early detection and location of leaks plays a major role in reducing losses. This can be conducted using vibro-acoustics techniques, but there are problems with plastic pipes compared to metallic pipes, especially when using leak noise correlators. This is because the leak noise that propagates through the pipe is heavily attenuated in plastic pipes reducing the amplitude and hence distance that this noise can propagate. Leak noise correlators use knowledge of the leak noise velocity and an estimate of the difference between the arrival times of the leak noise at two sensors placed on the pipe at available access points. Generally, the pipe geometry (wall thickness and pipe nominal radius) and its Young’s modulus have a profound effect on leak noise attenuation and velocity. Moreover, the surrounding medium also has an additional effect. In this paper some web-based software is described that simulates different scenarios to help users of leak noise correlators to understand the physics behind the problem and to help them select the properties of some filters that need to be set to obtain reliable results. The software is based on a wave-type model which takes into account the pipe vibration response due to excitation by a leak. Inputs to the model are the pipe geometry, material properties of the pipe and surrounding medium, distance between the sensors and sensor type (accelerometer, geophone and hydrophone). These parameters are then used to estimate the leak velocity, time delay, frequency bandwidth (CPSD-Cross-Power Spectral Density) and leak location, which are given in a user-friendly graphical interface.